2009
DOI: 10.4162/nrp.2009.3.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effect of garlic and aged black garlic in animal model of type 2 diabetes mellitus

Abstract: Hyperglycemia in the diabetic state increases oxidative stress and antioxidant therapy can be strongly correlated with decreased risks for diabetic complications. The purpose of this study is to determine antioxidant effect of garlic and aged black garlic in animal model of type 2 diabetes. The antioxidant activity of garlic and aged black garlic was measured as the activity in scavenging free radicals by the trolox equivalent antioxidant capacity (TEAC) assay. Three week-old db/db mice were fed AIN-93G diet o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
0
20

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(136 citation statements)
references
References 37 publications
(49 reference statements)
4
109
0
20
Order By: Relevance
“…Experiment animal studies (Lee et al, 2009) showed that aged black garlic exerts stronger antioxidant activity than garlic in vitro and in vivo, suggesting that garlic and aged black garlic could be useful in preventing diabetic complications to a greater extent. The meta-analysis results (Kook et al, 2009) of animal studies suggested that the single component intake and onion extract intake may be effective for lowering plasma glucose concentrations and body weight.…”
Section: Discussionmentioning
confidence: 97%
“…Experiment animal studies (Lee et al, 2009) showed that aged black garlic exerts stronger antioxidant activity than garlic in vitro and in vivo, suggesting that garlic and aged black garlic could be useful in preventing diabetic complications to a greater extent. The meta-analysis results (Kook et al, 2009) of animal studies suggested that the single component intake and onion extract intake may be effective for lowering plasma glucose concentrations and body weight.…”
Section: Discussionmentioning
confidence: 97%
“…Aged black garlic has been generally reported to have excellent antioxidant potency when compared to fresh or cooked garlic. The reason is probably that the bioactivity of some natural products increases during the process of fermentation [17][18][19][20][21][22][23], but no specific experimental proof has yet established its anti-cancer efficacy. In this study, we have demonstrated that HEABG significantly decreased cell proliferation in human leukemic U937 cells by inducing apoptosis, as determined by DAPI staining, agarose gel electrophoresis and flow cytometric analyses.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most useful garlic preparations is aged black garlic, which is produced by aging whole garlic at high temperature and humidity [17]. Previous studies have shown that the extracts of aged black garlic have many pharmacological activities, including antioxidant, radical scavenging and anti-cancer effects [17][18][19][20][21][22]. Recently, Kim et al [23] reported that a hexane extract of aged black garlic (HEABG) potently suppressed the proliferation of tumor necrosis factor (TNF)-α-activated human endometrial stromal cells, through inhibiting the activation of nuclear factor-κB (NF-κB) and activator protein-1 (AP-1) transcription factors.…”
Section: Introduction 2)mentioning
confidence: 99%
“…Bis(allixinato) oxovanadium(IV) was thus proposed to be one of the most effective candidates for antidiabetic therapy. In an animal model of type 2 diabetes, feeding of db/db mice for 7 weeks with aged black garlic exerted stronger antioxidant activity than normal garlic indicating the usefulness of black garlic in diabetic complications (Lee et al 2009b ). Consumption of aged black garlic signifi cantly decreased hepatic thiobarbituric acid reactive substances (TBARS) level compared with the garlic group which showed lower TBARS level than the control group.…”
Section: Antihyperglycaemic/antidiabetic Activitymentioning
confidence: 99%